Electronic support and research productivity: the case of academic engineers and scientists - Zainab, A.N.; Meadows, A.J. (1999)
Compares the frequency of eleven types of computer use with the publication produc-tivity of 83 academic engineers and 239 academic scientists from University of Malaya and National University of Malaysia. The data was collected from two sources. A self-administered questionnaire was used to obtain demographic data, their opinion on the adequacy of the computer facilities made available for them and the types of use they made of the computers for research purposes. Data on the total number and type of publications authored was obtained from the questionnaire, and the annual reports of academic staff publications for the years 1990 to1995. The results revealed that the majority of both academic engineers and scientists made frequent use of computers for research. However, the scientists indicated a more varied use than the engineers. Both groups reported frequent use of computers for word processing (83% to 90%), sending or receiving e-mails (66% to 71%) and searching for information in the Internet (41% to 51%). Computers are least used for keeping personal bibliographical indexes (8% to 11%). For the academic scientists, the total publication productivity is correlated (£0.01) to using computers for creating databases, word processing, slide presenta-tions, sending or receiving emails, obtaining information from the Internet and main-taining personal bibliographical indexes. For the academic engineers the total publication output is not correlated with frequent use of computers for research, although the mean score for each type of computer use is high. The frequency of computer use is also related to such factors as respondent's department, age, work experience and academic rank.